The role of accounting ethics in reducing financial corruption in economic institutions - bachiri, abdelalim; hadidi, Adam (Journal of Research in Finance and Accounting, 2022)
This study aimed to confirm the inverse relationship between the ethics of the accounting profession and the extent of financial corruption, Where the ethics of the accounting profession has been classified into the ethics of the personal accounting profession represented in (honesty, devotion, perfection, Behavior of faith (, and The ethics of the acquired accounting profession represented in (integrity, Objectivity, professional competence, confidentiality, professional behavior), To confirm the inverse relationship, regression models were used, where the questionnaire was relied on as a tool for data collection, which was analyzed by the SPSS.V26 program. The study found a statistically significant relationship between commitment to the ethics of the accounting profession and the extent of financial corruption at a significant level , And that the contribution of adherence to the ethics of the accounting profession in reducing the amount of financial corruption is estimated at a percentage 83,55%.